TRANSFORMING GROWTH FACTOR BETA-1 EXPRESSION AND CYTOTOXICITY OF COMBINATION CHITOSAN-HYDROXYAPATITE IN DIRECT PULP CAPPING - sularsih, sularsih (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2025)
Background: Chitosan is marine natural resources which potential to promote pulp healing. Combination chitosan-hydroxyapatite has ability to stimulate fibroblast cells proliferation. Purpose: The aim of this study was to analyze expression of TGF β1 and the cytotoxicity of chitosan-hydroxyapatite (CH-HA) in direct pulp capping treatment. Materials and Methods: It divided 5 groups pasta: control group, CH, HA, CH-HA (50:50) and CH-HA (80:20) groups. Each of sample was investigated cytotoxicity test by MTT assay method to analyze percentage of viability fibroblast cells. Experimental animals used 30 Rattus norvegicus strain wistar. Oclusal part Molar was perforated with tip of explorer then filled with GIC (group1), Ca (OH)2 (group2), CH (group3), HA (group4) and CH-HA (50:50) (group5). The mandibular bone was cut and Immunohistochemistry was carried out to examine TGF β1 expression on 3 days observation. Results: The result of analysis percentage of viability fibroblast cells in control group, CH, CH-HA (50:50) and CH-HA (80:20) uper 50 % using parameter CD50. Anova test showed expression of TGF β1 significant increased (p≤0.05) in group5 comparing among five groups and there was significant differences between the groups on expression TGF β1. Conclusion: The combination of CH-HA was nontoxic and it could accelerate pulp healing by increasing expression of TGF β1.